Hydrate growth model in the presence of thermodynamic inhibitors or promoters - Young, Ingrid Azevedo de Oliveira (2020)
There are scenarios in which hydrate formation is desired, such as in its technological application for gas storage or in natural reserves with potential sources of energy. There are other scenarios in which these solids formation is undesirable, as hydrate precipitation in pipelines causing flow assurance problems in the oil and gas industry. In both cases, an understanding of the thermodynamics and dynamics of the hydrate formation in the presence of chemical additives is essential. In this work, it is proposed to improve the calculation of hydrate equilibrium in the presence of a thermodynamic inhibitor, ethanol (EtOH), or a thermodynamic promoter, tetrahydrofuran (THF). The knowledge about hydrate equilibria is used to develop a kinetic model of growth capable of accounting the effects of additives, based on the non-equilibrium thermodynamics theory, and using chemical affinity as a driving force. As a result, adequate modeling of the double CH4/THF hydrate was obtained with a maximum deviation of 0.27% in the equilibrium temperature. Besides, 15 wt% of EtOH in the liquid phase was defined as the limited for its application only as an inhibitor by combining experimental results with equilibrium calculations. The effects of coupling diffusion and reaction on the CH4 hydrate growth in freshwater were mainly dependent on pressure. The kinetic model of CH4-hydrate growth in the presence of EtOH, including the effects of non-ideality, can describe the behavior of EtOH as a thermodynamic inhibitor and as a potential kinetic inhibitor, observed in the literature.